(-14i)(-8i)=0

Simple and best practice solution for (-14i)(-8i)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-14i)(-8i)=0 equation:


Simplifying
(-14i)(-8i) = 0

Remove parenthesis around (-14i)
-14i(-8i) = 0

Remove parenthesis around (-8i)
-14i * -8i = 0

Reorder the terms for easier multiplication:
-14 * -8i * i = 0

Multiply -14 * -8
112i * i = 0

Multiply i * i
112i2 = 0

Solving
112i2 = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Divide each side by '112'.
i2 = 0

Simplifying
i2 = 0

Take the square root of each side:
i = {0}

See similar equations:

| 68x-2=(50x+4)+15x | | 6y+3+3y-5= | | 5(1n-1)=7 | | 6=z/4-3 | | 11-5+5/-2 | | (8x+5)(8x+5)=4 | | 5y-2=2y-19 | | 431x=3574299 | | -2.3=u/4+4.1 | | 2(x+5)=10x-14 | | -35=x-5 | | 2=2+5v+2v | | -5-n=10 | | -3+12+6= | | 0.78=logx | | 8(x+1)=7(x+2) | | 2/7(21) | | 7(x-3)=8(4-2x) | | 5x-1=6x+7 | | 7(x-2)=-5 | | (2x+1)(3x-9)=0 | | 68x-25=(50x+4)+15x | | 52=3(-n-8)-2(1-8n) | | 47-y=205 | | 3n+6/3=5 | | 66=-6(-5+x) | | x^2+70x-1050=0 | | 5(2x+1)=10 | | 13x-4=12x-1 | | P=2l+2wfore | | 26=6(5-4*.1666666667) | | 15x-9=10x+1 |

Equations solver categories